EFEKTIFITAS PEMBELAJARAN KELAS IBU HAMIL (KIH) DALAM MENURUNKAN ANEMIA DI KECAMATAN GROGOL SUKOHARJO - muwakhidah, muwakhidah (Universitas Muhammadiyah Semarang, 2018)
Maternal deaths in developing countries one of the causes is anemia in pregnancy, an increasing proportion of pregnant women with anemia. One effort to prevent and overcome the occurrence of anemia in pregnant women is maternal class program which aims to increase knowledge and skill of mothers about pregnancy, childbirth, postpartum care and newborn care, through practice by using KIA book ( Child Mother Health). The purpose of this study is to determine the effectiveness of learning systems of pregnant mothers class in reducing of anemia in the District Grogol Sukoharjo District. This type of research is Quasi-Exsperimental Design, using Non Equivalent Control Group Design. Sampling by Consecutive sampling technique with the number of 40 respondents for each group. Measure of hemoglobin level using cyanmethemoglobin, and stattistic analysis using Mann-Whitney test. The result showed that the average of KIH and non KIH knowledge was 86.9 + 76.5, the mean of KIH and non KIH anemia was 11.9 g/dl and 11.2 g/dl Based on the result of statistical test, there is difference of knowledge between maternal and non pregnant class (p = 0,000), and there is difference of anemia between maternal and non pregnant class (p = 0,001)